2009
DOI: 10.1016/j.resp.2009.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Opioid μ-receptors in medullary raphe region affect the hypoxic ventilation in anesthetized rats

Abstract: Opioids can attenuate the peripheral chemoreceptor-mediated hypoxic ventilatory response (HVR) by acting on central μ-type opioid receptors. Since the medullary raphe region (MRRs) expresses abundant μ-receptors and participates in modulating HVR, we tested the role of μ-receptors within the caudal, medial, and rostral MRR (cMRR, mMRR, and rMRR) in modulating the HVR. We recorded cardiorespiratory activities and their responses to isocapnic hypoxia in anesthetized rats before and after local microinjection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…With respect to central HX pathways, it is known that microinjection of opioid μ-receptor agonists into the medullary raphe region (Zhang et al, 2009) and commissural NTS (Zhang et al, 2011) suppress HVR. Morphine has numerous potential sites/mechanisms to suppress ventilatory responses to HC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to central HX pathways, it is known that microinjection of opioid μ-receptor agonists into the medullary raphe region (Zhang et al, 2009) and commissural NTS (Zhang et al, 2011) suppress HVR. Morphine has numerous potential sites/mechanisms to suppress ventilatory responses to HC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, microinjections of the μ-OR agonist, DAMGO, into medullary raphe regions of anesthetized rats blunt HVR whereas microinjections of DAMGO into the commissural NTS suppress HVR and HCVR (Zhang et al, 2007, 2009, 2011). The ability of morphine to depress HVR (Berkenbosch et al, 1997; Dahan et al, 1988; Sarton et al, 1999) and HCVR (Sarton et al, 1999) in humans, suggests that opioids and/or metabolites of opioids (Peat et al, 1991) depress carotid body (CB) function and central mechanisms responsive to these challenges (Dahan et al, 1998; Sarton et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in rats have also demonstrated that opioids depress V M and ABG chemistry [3,7-12], blunt the ventilatory responses to hypoxic challenge [13], and depress carotid body chemoafferent responses to hypoxic or hypercapnic challenges [14-18]. It is rightfully assumed that ventilatory control processes per se and the ventilatory responses to hypoxic and/or hypercapnic challenges recover upon the amelioration of the effects of opioids on baseline ventilatory parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in animals have demonstrated that opioids also depress ventilation via central and peripheral effects [see 810] including central- [11] and vagal afferent-mediated [12] depression of ventilatory drive; skeletal muscle rigidity in the chest-wall [13]; and increases in pulmonary [14] and upper airway [15] resistances. Moreover, activation of central and peripheral μ-ORs blunt the hypoxic ventilatory response [16], and opioids such morphine depress the responsiveness of carotid body chemoafferents to hypoxia and hypercapnia [1719]. …”
Section: Introductionmentioning
confidence: 99%